Bioclimatic Characterization Relating to Temperature and Subsequent Future Scenarios of Vine Growing across the Apulia Region in Southern Italy - Giovanni Gentilesco; Antonio Coletta; Luigi Tarricone; Vittorio Alba (Agriculture, 2023)
The progressive climate change has an impact on the quantity and quality of grapes. Among meteorological parameters, air temperature is believed to have a direct influence on grape yield and composition, as well as on the organoleptic characteristics of wines. Therefore, in this work three bioclimatic indices based on temperature have been considered, with the aim of classifying the climate in the winegrowing region of Apulia (southern Italy) based on historical periods of thirty years (1961–1990 and 1991–2022) and verifying its evolution in the future in relation to global warming under two different Shared Socioeconomic Pathways, SSP2–4.5 and SSP5–8.5, by combining four global climate models. The results showed that the period 2021–2040 was almost unchanged compared to the last historical period of 1991–2022. The differences between the two SSPs became more pronounced as time progressed until the end of this century. By 2081–2100, SSP2–4.5, considered the most likely and mildest future scenario, demonstrated the existence of areas still suitable for quality viticulture, mainly in the higher altitudes of the Murgia plateau, the Gargano promontory and the Pre–Apennine area. In contrast, SSP5–8.5, described as “highly unlikely”, showed a dramatic shift of more than 90% of Apulia region to “too hot” classes to ensure the survival of viticulture for all the bioclimatic indices considered. These results suggest the winegrowers should consider short– and long–term solutions and adaptations in order to preserve the regional tradition and wine quality and to plan the Apulian viticulture for future scenarios.